Effectiveness and safety of 12-month certolizumab pegol treatment for axial spondyloarthritis in real-world clinical practice in Europe. (25th June 2020) - Baraliakos, Xenofon; Witte, Torsten; De Clerck, Luc; Frediani, Bruno; Collantes-Estévez, Eduardo; Katsifis, Gkikas; VanLunen, Brenda; Kleine, Elisabeth; Hoepken, Bengt; Bauer, Lars; Goodson, Nicola
Abstract: Objectives: The efficacy and safety of certolizumab pegol (CZP), an Fc-free, PEGylated anti-TNF, in axial spondyloarthritis (axSpA) has been established in clinical trial settings. We report CZP effectiveness and safety in European clinical practice in patients with axSpA, including radiographic (r-) and non-radiographic (nr-) axSpA. Methods: CIMAX (NCT02354105), a European non-interventional multicentre prospective study, observed CZP treatment response and safety over 12 months in a real-world axSpA cohort. The primary outcome was change from baseline in BASDAI to week 52, with additional outcomes pertaining to effectiveness and safety. Patients who received ≥1 dose CZP were followed up for adverse events, and those with baseline and ≥1 post-baseline BASDAI assessment were included in effectiveness analyses. Results: A total of 672 patients (r-axSpA: 469; nr-axSpA: 201; unconfirmed diagnosis: 2) from 101 sites received ≥1 dose of CZP, of whom 564 (r-axSpA: 384; nr-axSpA: 179; unconfirmed: 1) were included in the effectiveness analyses. The mean baseline BASDAI was 6.1 in the overall axSpA population and r-axSpA and nr-axSpA subpopulations. At week 52, the mean (s .d .) change in BASDAI was −2.9 (2.3; n  = 439); for r-axSpA and nr-axSpA, it was −2.9 (2.2; n  = 301) and −2.8 (2.4; n  = 137), respectively ( P  <0.0001 for all). Similar improvements were seen across other axSpA disease measures. In total, 37.9% (255/672) patients experienced adverse events, and 1.8% (12/672) experienced ≥1 serious adverse events. Conclusion: Improvements observed in signs and symptoms of axSpA following one year of CZP treatment in real-world clinical practice were similar to those from previous randomized clinical trials, with no new safety concerns.